Land‐use change shifts and magnifies seasonal variations of the decomposer system in lowland tropical landscapes. Issue 6 (17th June 2022) - Krashevska, Valentyna; Stiegler, Christian; June, Tania; Widyastuti, Rahayu; Knohl, Alexander; Scheu, Stefan; Potapov, Anton
Abstract: Deforestation and agricultural expansion in the tropics affect local and regional climatic conditions, leading to synergistic negative impacts on land ecosystems. Climatic changes manifest in increased inter‐ and intraseasonal variations and frequency of extreme climatic events (i.e., droughts and floods), which have evident consequences for aboveground biodiversity. However, until today, there have been no studies on how land use affects seasonal variations below ground in tropical ecosystems, which may be more buffered against climatic variation. Here, we analyzed seasonal variations in soil parameters, basal respiration, microbial communities, and abundances of soil invertebrates along with microclimatic conditions in rainforest and monocultures of oil palm and rubber in Sumatra, Indonesia. About 75% (20 out of 26) of the measured litter and soil, microbial, and animal parameters varied with season, with seasonal changes in 50% of the parameters depending on land use. Land use affected seasonal variations in microbial indicators associated with carbon availability and cycling rate. The magnitude of seasonal variations in microbial parameters in the soil of monocultures was almost 40% higher than in the soil of rainforest. Measured parameters were associated with short‐term climatic conditions (3‐day period air humidity) in plantations, but not in rainforest, confirming a reduced soil buffering ability in plantations. Overall, our findings suggest that land use temporally shifts and increases the magnitude of seasonal variations of the belowground ecosystem compartment, with microbial communities responding most strongly. The increased seasonal variations in soil biota in plantations likely translate into more pronounced fluctuations in essential ecosystem functions such as nutrient cycling and carbon sequestration, and these ramifications ultimately may compromise the stability of tropical ecosystems in the long term. As the observed seasonal dynamics is likely to increase with both local and global climate change, these shifts need closer attention for the long‐term sustainable management of plantation systems in the tropics. Abstract : Land use shifted seasonal changes in microbial, animal, and bulk soil parameters. The magnitude of soil microbial variation increased by 40% in monocultures. The soil system in monocultures is affected by short‐term microclimatic changes. Increased seasonal variation in soil functioning is an aspect of global change.